Case report: Complex left-carina resection: three-year single-center experience - Tombelli, Simone; Viggiano, Domenico; Salimbene, Ottavia; Trigiani, Marco; Voltolini, Luca; Gonfiotti, Alessandro (Frontiers in Oncology, 2024)
Carinal and tracheobronchial angle tumors have long been a contraindication for surgical removal; the technique of tracheal sleeve pneumonectomy makes it possible to approach this malignancy, but still represents a surgical challenge. Left sleeve pneumonectomy is less common compared to right sleeve pneumonectomy and represent a minority component in the literature's case series due to the complexity of the anatomy. In addition, there is no standard for treatment strategy and it must be assessed on a case-by-case basis. From 2020 to 2023, we performed three left tracheal sleeve pneumonectomies and one neocarina reconstruction surgery for benign lesions without lung resections. All cases were performed without cardiovascular support such as cardiopulmonary bypass (CPB) and via median sternotomy. With a median length of stay of 21.5 days (between 14 and 40 days), all patients were transferred to a physiotherapeutic rehabilitation facility for functional reactivation, where they received physiotherapeutic respiratory therapy given the slow functional recovery. The recorded 30-day mortality was 0.There is no standardized approach for left-sided sleeve pneumonectomy and it is still a surgical challenge due to intraoperative and postoperative difficulties.